2009
DOI: 10.1111/j.1748-0361.2009.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Recruitment Paths of Certified Nursing Assistants in Rural and Urban Nursing Homes

Abstract: Career-changers (individuals entering the CNA role from another job) represent a major recruitment target. The prevalence of informal networks in CNA recruitment history suggests that nursing homes seeking to become "employers of choice" will be advantaged when recruiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Perceived as excellent by 41.9 % to 44.6 % of HCAs [ 21 ] Provider and policy : Personal safety, emergency procedures, infection control, service policy/protocol, risk management, fire and safety [ 26 ], record resident information, prevent work injuries, organize tasks, work with supervisors, work with coworkers, problems-solve work issues [ 21 , 33 ]. Perceived as excellent by 32.2 % to 52.8 % of HCAs [ 21 ] Requested topics for initial training Patient care : Care skills [ 21 , 29 ], talk with residents, medication management, pain management [ 21 ] Holistic care : Abusive residents [ 21 , 29 ], discuss resident care with family members, work with residents family, dementia care [ 21 ], mental health training, integrating health promotion, multicultural training, challenging behavior skills [ 29 ] Provider and policy : Work with coworkers, organize work tasks, work with supervisors, problem solving for work issues, record resident information, prevent work injuries [ 21 ], physical preparation for the role, training in management, stress management [ 29 ] Location of initial or vocational training (range) Facility employing: 43.1 %, among immigrants [ 33 ] to 65.3 %, rural [ 53 ] Community college 15.7 %, among immigrants [ 33 ] to 23.8 %, micropolitan [ 53 ] High school: 6.0 %, micropolitan setting to 6.3 %, rural [ 53 ] Vocational or trade school: 5.4 %, micropolitan to 6.6 %, urban [ 53 ] Cost of training (range) Entirely paid for by employer: 67.9 %, urban [ 53 ] to 78 % [ 28 ] Training hours (range) Ratio classroom to clinical: 50:50 [ 69 ] to 95:5, in “other” long-term care settings [ 14 ] Qualification National Vocational Qualification (UK): 4 levels of qualification [ 18 , 42 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived as excellent by 41.9 % to 44.6 % of HCAs [ 21 ] Provider and policy : Personal safety, emergency procedures, infection control, service policy/protocol, risk management, fire and safety [ 26 ], record resident information, prevent work injuries, organize tasks, work with supervisors, work with coworkers, problems-solve work issues [ 21 , 33 ]. Perceived as excellent by 32.2 % to 52.8 % of HCAs [ 21 ] Requested topics for initial training Patient care : Care skills [ 21 , 29 ], talk with residents, medication management, pain management [ 21 ] Holistic care : Abusive residents [ 21 , 29 ], discuss resident care with family members, work with residents family, dementia care [ 21 ], mental health training, integrating health promotion, multicultural training, challenging behavior skills [ 29 ] Provider and policy : Work with coworkers, organize work tasks, work with supervisors, problem solving for work issues, record resident information, prevent work injuries [ 21 ], physical preparation for the role, training in management, stress management [ 29 ] Location of initial or vocational training (range) Facility employing: 43.1 %, among immigrants [ 33 ] to 65.3 %, rural [ 53 ] Community college 15.7 %, among immigrants [ 33 ] to 23.8 %, micropolitan [ 53 ] High school: 6.0 %, micropolitan setting to 6.3 %, rural [ 53 ] Vocational or trade school: 5.4 %, micropolitan to 6.6 %, urban [ 53 ] Cost of training (range) Entirely paid for by employer: 67.9 %, urban [ 53 ] to 78 % [ 28 ] Training hours (range) Ratio classroom to clinical: 50:50 [ 69 ] to 95:5, in “other” long-term care settings [ 14 ] Qualification National Vocational Qualification (UK): 4 levels of qualification [ 18 , 42 ...…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies were relevant to HCA education [ 14 , 15 , 18 , 19 , 21 , 25 , 26 , 28 , 29 , 33 36 , 40 , 42 – 45 , 47 , 52 , 53 , 56 , 69 , 71 , 72 ]. Common reasons for becoming an HCA, ranked by North American HCAs in order of importance, were: 1) a desire to help [ 33 , 53 ] or an inclination to work with people [ 41 ], 2) an aspiration to work in health care [ 33 , 53 ], and 3) job security [ 33 , 53 ] or related, desirable job benefits [ 41 ]. Transitions into HCA professions were explored in two U.S.-based studies [ 53 , 72 ]: one [ 72 ] reported that 28.8 % of those newly entering the HCA workforce had most recently been unemployed (unrelated to disability).…”
Section: Resultsmentioning
confidence: 99%
“…In 2006, 15% of RNs were non-white, and 29% of LPNs were non-white (Lacey & McNoldy, 2007; Probst, Baek, & Laditka, 2009). According to National Nursing Home Survey Data, 46% of CNAs nationally are non-white, and 24% of CNAs nationally have preparation at the community college or trade school level or are college graduates (Probst, et al, 2009; Squillace et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The current study was conducted in a rural area and may not be applicable to urban or suburban settings. Previous research (Probst et al. 2009) found that rural areas face different challenges when dealing with the LTC of their elderly than their urban counterparts.…”
Section: Limitationsmentioning
confidence: 98%